Age and gender effects on presence, user experience and usability in virtual environments–first insights - Lorenz, Mario; Brade, Jennifer; Klimant, Philipp; Heyde, Christoph-E.; Hammer, Niels (PLOS ONE, 2023)
Virtual Reality (VR) is applied in various areas were a high User Experience is essential. The sense of Presence while being in VR and its relation to User Experience therefore form crucial aspects, which are yet to be understood. This study aims at quantifying age and gender effects on this connection, involving 57 participants in VR, and performing a geocaching game using a mobile phone as experimental task to answer questionnaires measuring Presence (ITC-SOPI), User Experience (UEQ) and Usability (SUS). A higher Presence was found for the older participants, but there was no gender difference nor any interaction effects of age and gender. These findings are contractionary to preexisting limited work which has shown higher Presence for males and decreases of Presence with age. Four aspects discriminating this study from literature are discussed as explanations and as a starting point for future investigations into the topic. The results further showed higher ratings in favor of User Experience and lower ratings towards Usability for the older participants.